2023
DOI: 10.7759/cureus.42021
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum and Preterm Babies: A Systematic Review

Ethan Slouha,
Zoe S Anderson,
Nana Mansa N Ankrah
et al.

Abstract: Colostrum from mothers is rich in immunomodulating bio-factors such as immunoglobulins (IgA), lactoferrin, and oligosaccharides and supports gut microbial and inflammatory processes. The support in these processes may provide some relief for infants who are born pre-term. Pre-term infants are more likely to develop necrotizing enterocolitis (NEC), late-onset sepsis (LOS), and ventilator-acquired/associated pneumonia (VAP). Due to the components of colostrum, there may be incentives towards early administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In some cultures, discarding colostrum has been practiced [ 125 ], but the biological and clinical importance of human colostrum has received much attention, especially for the most vulnerable, preterm infants. Recent meta-analyses and systemic reviews showed that even very small amounts of a mother’s colostrum reduce the incidences of colitis, sepsis, lung disease, feeding problems, and growth deficits [ 126 , 127 ]. These findings are supported by some reviews [ 128 ], but questioned in others [ 129 ], and the mechanisms underlying this are unknown.…”
Section: Colostrum Bioactivitymentioning
confidence: 99%
“…In some cultures, discarding colostrum has been practiced [ 125 ], but the biological and clinical importance of human colostrum has received much attention, especially for the most vulnerable, preterm infants. Recent meta-analyses and systemic reviews showed that even very small amounts of a mother’s colostrum reduce the incidences of colitis, sepsis, lung disease, feeding problems, and growth deficits [ 126 , 127 ]. These findings are supported by some reviews [ 128 ], but questioned in others [ 129 ], and the mechanisms underlying this are unknown.…”
Section: Colostrum Bioactivitymentioning
confidence: 99%
“…We may have been unaware of it, but likely full-term infant self-attachment supported by the Baby Friendly Hospital Initiative has led to this normal biological benefit ( Garofoli et al, 2023 ). However, the role of colostrum has been downplayed by our current separation paradigm, and it deserves greater attention, especially for the preterm neonate ( Slouha et al, 2023 ).The first hour colostrum will almost certainly contain high levels of oxytocin, and this has an important role in multiple gastrointestinal functions that are subjected to neuronal regulation ( Welch et al, 2014a ). The enterocytes (stomach lining) have been shown to have oxytocin receptors, contributing to early protection against inflammation ( Gross Margolis et al, 2017 ).…”
Section: New Perspectives On Kmcmentioning
confidence: 99%